Thermoelectric conversion materials and thermoelectric conversion elements
Patent Information
- Application Number
- JP2021105672
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-25
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2041-06-25
AI Technical Summary
【0019】 本発明により、良好なゼーベック係数と導電性との両立を達成する熱電変換材料を提供することができる。また、優れた熱電性能を発揮する熱電変換素子を提供することができる。
Smart Images

Figure 0007635651000001 
Figure 0007635651000002 
Figure 0007635651000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoelectric conversion material and a thermoelectric conversion element. [Background technology]
[0002] Thermoelectric materials that can convert between thermal energy and electrical energy are used in thermoelectric conversion elements such as thermoelectric generators and Peltier elements. Thermoelectric conversion elements are elements that convert heat into electricity and are made up of a combination of semiconductors and metals. Representative thermoelectric conversion elements are classified into p-type semiconductors alone, n-type semiconductors alone, and combinations of p-type and n-type semiconductors. Thermoelectric conversion elements utilize the Seebeck effect, which generates an electromotive force when heat is applied to create a temperature difference between both ends of a semiconductor. To obtain a larger potential difference, thermoelectric conversion elements generally use a combination of p-type and n-type semiconductors as materials.
[0003] Thermoelectric conversion elements are also used as thermoelectric modules, which are made by combining a number of elements into a plate or cylinder shape. They can directly convert thermal energy into electricity, and can be used, for example, as a power source for wristwatches that operate with body heat, and for power generation on the ground and in artificial satellites. The performance of a thermoelectric conversion element depends on the performance of the thermoelectric conversion material and the durability of the module.
[0004] As described in Non-Patent Document 1, the dimensionless thermoelectric figure of merit (ZT) is used as an index representing the performance of a thermoelectric conversion material. In addition, the power factor PF (=S 2 ·σ) may also be used. The dimensionless thermoelectric figure of merit "ZT" is expressed by the following formula (1). ZT=(S 2 σ T) / κ Equation (1) Here, S is the Seebeck coefficient (V / K), σ is the electrical conductivity (S m), T is the absolute temperature (K), and κ is the thermal conductivity (W / (m K)). Thermal conductivity κ is expressed by the following equation (2). κ = α ρ C Equation (2) where α is the thermal diffusivity (m 2 / s), ρ is density (kg / m 3 ), and C is the specific heat capacity (J / (kg K)). That is, in order to improve the thermoelectric conversion performance (hereinafter also referred to as thermoelectric properties), it is important to improve the Seebeck coefficient or electrical conductivity while decreasing the thermal conductivity.
[0005] Representative thermoelectric conversion materials include inorganic materials such as bismuth-tellurium (Bi-Te) for temperatures from room temperature to 500 K, lead-tellurium (Pb-Te) for temperatures from room temperature to 800 K, and silicon-germanium (Si-Ge) for temperatures from room temperature to 1000 K.
[0006] However, thermoelectric conversion materials containing these inorganic materials often contain rare elements and are expensive, or may contain harmful substances. In addition, inorganic materials are poorly processable, which makes the manufacturing process complicated. Therefore, the manufacturing energy and manufacturing costs of thermoelectric conversion materials containing inorganic materials are high, making it difficult to generalize them. Furthermore, inorganic materials are rigid, so it is difficult to form flexible thermoelectric conversion elements that can be installed on shapes that are not flat.
[0007] In response to this, research is being conducted into thermoelectric conversion elements that use organic materials instead of conventional inorganic materials. Organic materials have excellent moldability and are more flexible than inorganic materials, so they are highly versatile within the temperature range in which they do not decompose. In addition, they are more advantageous than inorganic materials in terms of manufacturing energy and costs, as they can be easily produced using printing techniques and other methods.
[0008] For example, Patent Document 1 describes a thermoelectric material in which an organic dye skeleton is bonded to a polymer dispersant and contained together with carbon nanotubes (CNTs), thereby providing good CNT dispersibility, suitability for coating methods, and excellent thermoelectric power. Patent Document 2 describes a thermoelectric conversion material in which a porphyrin skeleton is bonded to a substituent containing an alkyl group, and which exhibits a high Seebeck coefficient. However, in the invention of Patent Document 1, the polymer chain of the polymer dispersant inhibits interaction with the CNTs, and sufficient performance is not obtained. In addition, in the invention of Patent Document 2, the conductivity is 10 -8 ~10 -7 The electrical conductivity is low at only S / cm, and it is not possible to obtain a practical value for use as a thermoelectric element. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] International Publication No. 2015 / 050113 [Patent Document 2] International Publication No. 2015 / 129877 [Non-patent literature]
[0010] [Non-Patent Document 1] Takenobu Kajikawa, "Thermoelectric Conversion Technology Handbook (First Edition)", NTS Publishing, p.19 Summary of the Invention [Problem to be solved by the invention]
[0011] The problem to be solved by the present invention is to provide a thermoelectric conversion material that achieves both a good Seebeck coefficient and electrical conductivity and exhibits a high power factor, and also to provide a thermoelectric conversion element that exhibits excellent thermoelectric performance. [Means for solving the problem]
[0012] The present inventors have conducted extensive research to solve the above problems and have arrived at the present invention. That is, the present invention relates to a thermoelectric conversion material comprising a conductive material A and an organic semiconductor B, the organic semiconductor B being represented by the following general formula (1).
[0013] [ka]
[0014] [In the general formula (1), m and n each independently represent an integer of 1 to 12. 1 , R 2 , R 3 , R 4 , R 5 and R 6 each independently represents an alkyl group, R 1 , R 2 and R 3 Any two or more of the above and R 4 , R 5 and R 6 Any two or more of X may be bonded to each other directly or via an oxygen atom to form a ring. - represents an anion. Y 1 and Y 2 each independently represents an oxygen atom, an oxyalkylene group, -COO-, -CONH-, or a divalent linking group formed by these groups.
[0015] The present invention also relates to the above thermoelectric conversion material, wherein the content of the organic semiconductor B is 10 to 100 mass % based on the total amount of the conductive material A.
[0016] The present invention also relates to the above thermoelectric conversion material, wherein m and n are each independently an integer of 1 to 7.
[0017] The present invention also provides X - is a halide ion.
[0018] The present invention also relates to a thermoelectric conversion element having a thermoelectric conversion film made of the above thermoelectric conversion material and electrodes, the thermoelectric conversion film and the electrodes being electrically connected to each other. Effect of the Invention
[0019] According to the present invention, it is possible to provide a thermoelectric conversion material that achieves both a good Seebeck coefficient and good electrical conductivity, and also to provide a thermoelectric conversion element that exhibits excellent thermoelectric performance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] <Thermoelectric conversion materials> The thermoelectric conversion material of the present invention is characterized by containing a conductive material A and an organic semiconductor B having a specific structure. Hereinafter, an embodiment of the present invention will be described in detail.
[0021] <Conductive material A> The conductive material A contributes to improving the conductivity. Examples of the conductive material A include carbon materials, metal materials, conductive polymers, etc. that have conductivity. For example, carbon materials include graphite, carbon nanotubes, Ketjen black, graphene nanoplates, graphene, etc. Examples of the metal materials include metal powders such as gold, silver, copper, nickel, chromium, palladium, rhodium, ruthenium, indium, silicon, aluminum, tungsten, molybdenum, germanium, gallium, and platinum, as well as ZnSe, CdS, InP, GaN, SiC, SiGe, and alloys and composite powders of these. Examples of the conductive material A include fine particles that are coated with a core and a material different from the core material, specifically, for example, silver-coated copper powder in which the core material is copper and the surface is coated with silver. Examples of the conductive material A include powders of metal oxides such as silver oxide, indium oxide, tin oxide, zinc oxide, ruthenium oxide, ITO (tin-doped indium oxide), AZO (aluminum-doped zinc oxide), and GZO (gallium-doped zinc oxide), as well as powders surface-coated with these metal oxides. Examples of conductive polymers include PEDOT / PSS (a composite of poly(3,4-ethylenedioxythiophene) (PEDOT) and polystyrene sulfonic acid (PSS)), polyaniline, polyacetylene, polypyrrole, polythiophene, polyparaphenylene, etc. The type of conductive material A used may be one type, or two or more types may be used in combination.
[0022] The shape of the conductive material A is not particularly limited, and shapes such as amorphous, aggregated, scaly, microcrystalline, spherical, flake, and wire shapes can be appropriately used.
[0023] From the viewpoint of achieving both a high Seebeck coefficient and high electrical conductivity, at least one selected from the group consisting of carbon nanotubes, Ketjen black, graphene nanoplates, and graphene is preferred, more preferably carbon nanotubes, and particularly preferably single-walled carbon nanotubes.
[0024] Examples of the conductive material A include flake graphite such as CMX, UP-5, UP-10, UP-20, UP-35N, CSSP, CSPE, CSP, CP, CB-150, CB-100, ACP, ACP-1000, ACB-50, ACB-100, ACB-150, SP-10, SP-20, J-SP, SP-270, HOP, GR-60, LEP, F#1, and Examples of the graphite include F#2, F#3, BF-3AK, FBF, BF-15AK, CBR, CPB-6S, CPB-3, 96L, 96L-3, K-3, SC-120, SC-60, HLP, CP-150, and SB-1 manufactured by Chuetsu Graphite Industry Co., Ltd., EC1500, EC1000, EC500, EC300, EC100, and EC50 manufactured by Ito Graphite Industry Co., Ltd., and 10099M and PB-99 manufactured by Nishimura Graphite Co., Ltd. Examples of the spherical natural graphite include CGC-20, CGC-50, CGB-20, and CGB-50 manufactured by Nippon Graphite Industry Co., Ltd. Examples of the amorphous graphite include Ao-P, AP, AOP, and P#1 manufactured by Nippon Graphite Industry Co., Ltd., and APR, K-5, AP-2000, AP-6, 300F, and 150F manufactured by Chuetsu Graphite Co., Ltd. Examples of artificial graphite include PAG-60, PAG-80, PAG-120, PAG-5, HAG-10W, and HAG-150 manufactured by Nippon Graphite Industries Co., Ltd.; G-4AK, G-6S, G-3G-150, G-30, G-80, G-50, SMF, EMF, SFF, SFF-80B, SS-100, BSP-15AK, BSP-100AK, and WF-15C manufactured by Chuetsu Graphite Co., Ltd.; and SGP-100, SGP-50, SGP-25, SGP-15, SGP-5, SGP-1, SGO-100, SGO-50, SGO-25, SGO-15, SGO-5, SGO-1, SGX-100, SGX-50, SGX-25, SGX-15, SGX-5, and SGX-1 manufactured by SEC Carbon Co., Ltd.Examples of commercially available carbon black include Tokai Carbon's Tokablack #4300, #4400, #4500, and #5500; Degussa's Printex L; and Colombian's Raven7000, 5750, 5250, 5000ULTRAIII, 5000ULTRA, Conductex SC ULTRA, and Conductex 975. Examples of furnace blacks include ULTRA, PUERBLACK 100, 115, and 205; #2350, #2400B, #2600B, #3050B, #3030B, #3230B, #3350B, #3400B, and #5400B manufactured by Mitsubishi Chemical Corporation; MONARCH 1400, 1300, 900, Vulcan XC-72R, and Black Pearls 2000 manufactured by Cabot Corporation; Ensaco 250G, Ensaco 260G, Ensaco 350G, and Super P-Li manufactured by TIMCAL Corporation; Ketjen blacks such as EC-300J and EC-600JD manufactured by Lion Corporation; and acetylene blacks such as Denka Black, Denka Black HS-100, and FX-35 manufactured by Denki Kagaku Kogyo Co., Ltd. Examples of commercially available conductive carbon fibers and carbon nanotubes include vapor grown carbon fibers such as VGCF manufactured by Showa Denko K.K., single-walled carbon nanotubes such as EC1.5 and EC1.5-P manufactured by Meijo Nano Carbon Co., Ltd., TUBALL manufactured by Kusumoto Chemicals Co., Ltd., and ZEONANO manufactured by Zeon Nano Technology Co., Ltd., FloTube9000, FloTube7000, and FloTube2000 manufactured by CNano Co., Ltd., NC7000 manufactured by Nanocyl Co., Ltd., and 100T and 200P manufactured by Knano Co., Ltd. These are not particularly limited, and may be used alone or in combination of two or more kinds.
[0025] <Organic Semiconductor B> Organic semiconductor B has a structure represented by general formula (1). It is believed that the phenylthiazolothiazole skeleton portion in general formula (1) improves thermoelectric conversion performance by adsorbing to the surface of conductive material A. In addition, it is believed that the quaternary ammonium cation portion in general formula (1) contributes to electrostatic repulsion of conductive material A in the thermoelectric conversion material, thereby improving dispersion stability and electrical conductivity.
[0026] The organic semiconductor B contributes to improving the Seebeck coefficient in the thermoelectric conversion material. From the viewpoint of achieving both the Seebeck coefficient and the electrical conductivity, the content of the organic semiconductor B is preferably 400% by mass or less, more preferably 200% by mass or less, even more preferably 120% by mass or less, and particularly preferably 100% by mass or less, based on the total amount of the conductive material A. Also, it is preferably 3% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more.
[0027] In order to promote surface adsorption and uniformity to the conductive material A and to increase the molecular ratio, the molecular weight of the organic semiconductor B is preferably small, preferably 2,000 or less, and more preferably 1,000 or less.
[0028] Here, the partial structure in the general formula (1) will be described. The linking group Y 1 and Y 2 represents an oxygen atom, an oxyalkylene group, -COO-, -CONH-, or a divalent linking group formed by bonding these. Among these linking groups, an oxygen atom and -COO- are preferred from the viewpoint of improving the dispersion stability and electrical conductivity of the conductive material.
[0029] In the organic semiconductor B, the linking group and the quaternary ammonium cation moiety are bonded via a linear alkylene group having 1 to 12 carbon atoms. m and n, which represent the chain lengths of the alkylene group, are 1 to 12, and preferably 1 to 7, from the viewpoint of improving thermoelectric performance.
[0030] The organic semiconductor B has an anion as a counter ion of the quaternary ammonium present in the molecule. The anion is not particularly limited, and examples thereof include halide ions such as fluoride ions, chloride ions, bromide ions, and iodide ions, carboxylate anions such as hydroxide ions, formate ions, acetate ions, and propionate ions, carbonate ions, sulfate ions, nitrate ions, chlorate ions, tetrafluoroborate ions, and tetrakispentafluorophenylborate ions. Among these anions, halide ions are preferred from the viewpoint of improving the dispersion stability and conductivity of the conductive material A.
[0031] R on quaternary ammonium 1 , R 2 , R 3 , R 4 , R 5 , and R 6 Each independently represents an alkyl group, and R 1 , R 2 and R 3 Any two or more of the above and R 4 , R 5 and R 6 Any two or more of these may be bonded to each other directly or via an oxygen atom to form a ring. As the alkyl group, an alkyl group having 1 to 4 carbon atoms, such as a methyl group, an ethyl group, a propyl group, or a butyl group, is preferred from the viewpoint of improving electrical conductivity and thermoelectric conversion properties.
[0032] <Other ingredients> The thermoelectric conversion material of the present invention may contain other components as necessary from the viewpoint of improving its properties. For example, by containing the other components exemplified below, it is possible to further improve the coatability, electrical conductivity, and thermoelectric properties.
[0033] (Organic semiconductors other than organic semiconductor B) The thermoelectric conversion material of the present invention may have an organic semiconductor other than the organic semiconductor B. The organic semiconductor other than the organic semiconductor B is not particularly limited, and examples thereof include phenylthiazolothiazole other than the organic semiconductor B and derivatives thereof, perylene and derivatives thereof, diketopyrrolopyrrole and derivatives thereof, and azo dyes and derivatives thereof.
[0034] (solvent) The solvent is used as a solvent or dispersion medium for uniformly mixing the conductive material A and the organic semiconductor B, and enables improvement of the coating properties by forming an ink. The solvent that can be used is not particularly limited as long as it can dissolve or disperse the conductive material A and the organic semiconductor B, and examples of the solvent that can be used include organic solvents and water, and two or more of them may be used in combination. The organic solvent may be appropriately selected as necessary from, for example, alcohols such as methanol, ethanol, propanol, butanol, ethylene glycol methyl ether, diethylene glycol methyl ether, terpineol, dihydroterpineol, 2,4-diethyl-1,5-pentanediol, 1,3-butylene glycol, and isobornylcyclohexanol, ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, ethers such as tetrahydrofuran, dioxane, ethylene glycol dimethyl ether, and diethylene glycol dimethyl ether, aliphatic hydrocarbons such as hexane, heptane, and octane, aromatic hydrocarbons such as benzene, toluene, xylene, and cumene, esters such as ethyl acetate and butyl acetate, and N-methylpyrrolidone. As the solvent, N-methylpyrrolidone is particularly preferred.
[0035] (auxiliary agent) Usable auxiliary agents are not particularly limited, and examples thereof include lactams, alcohols, aminoalcohols, carboxylic acids, acid anhydrides, and ionic liquids. Specific examples are as follows. Lactams: pyrrolidone, caprolactam, N-methylcaprolactam, and N-octylpyrrolidone. Alcohols: sucrose, glucose, fructose, lactose, sorbitol, mannitol, xylitol, glycerin, polyethylene glycol, polypropylene glycol, trifluoroethanol, m-cresol, thiodiglycol, and the like. Amino alcohols: diethanolamine, triethanolamine, etc. Carboxylic acids: 2-furancarboxylic acid, 3-furancarboxylic acid, dichloroacetic acid, trifluoroacetic acid, and the like. Acid anhydrides: acetic anhydride, propionic anhydride, acrylic anhydride, methacrylic anhydride, benzoic anhydride, succinic anhydride, maleic anhydride, itaconic anhydride, glutaric anhydride, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride (also known as cyclohexane-1,2-dicarboxylic anhydride), trimellitic anhydride, hexahydrotrimellitic anhydride, pyromellitic anhydride, himic anhydride, biphenyltetracarboxylic anhydride, 1,2,3,4-butanetetracarboxylic anhydride, naphthalenetetracarboxylic anhydride, and 9,9-fluorenylidenebisphthalic anhydride, etc. Copolymers of maleic anhydride and other vinyl monomers, such as styrene-maleic anhydride copolymer, ethylene-maleic anhydride copolymer, isobutylene-maleic anhydride copolymer, and alkyl vinyl ether-maleic anhydride copolymer.
[0036] From the viewpoint of electrical conductivity and thermoelectric properties, it is preferable to use at least one of lactams and alcohols as the auxiliary. The content of the auxiliary is preferably in the range of 0.1 to 30 mass%, more preferably in the range of 1 to 10 mass%, and even more preferably in the range of 1 to 5 mass%, based on the total mass of the thermoelectric conversion material. By making the content of the auxiliary 0.1 mass% or more, it is possible to easily obtain the effect of improving the electrical conductivity and thermoelectric properties. Furthermore, when the content of the auxiliary is 50 mass% or less, it is possible to suppress the deterioration of the film properties.
[0037] (resin) The thermoelectric conversion material of the present invention may contain a resin to the extent that it does not affect the electrical conductivity and thermoelectric properties, for the purpose of adjusting the film formability and film strength. The resin is preferably one that can be compatible with or uniformly dispersed in each component of the thermoelectric conversion material. Either a thermosetting resin or a thermoplastic resin may be used. Specific examples of resins that can be used include polyester resins, polyimide resins, polyamide resins, fluororesins, vinyl resins, epoxy resins, xylene resins, aramid resins, polyurethane resins, polyurea resins, melamine resins, phenolic resins, polyether resins, acrylic resins, acrylamide resins, and copolymer resins thereof. Although not particularly limited, in one embodiment, it is preferable to use at least one selected from the group consisting of polyurethane resins, polyether resins, acrylic resins, and acrylamide resins.
[0038] <Thermoelectric conversion element> The thermoelectric conversion element of the present invention is characterized in that it is constructed using the above-mentioned thermoelectric conversion material. In one embodiment, the thermoelectric conversion element has a thermoelectric conversion film formed using the above-mentioned thermoelectric conversion material and electrodes, and the thermoelectric conversion film and the electrodes are electrically connected to each other. The thermoelectric conversion film is excellent in heat resistance and flexibility in addition to electrical conductivity and thermoelectric properties. Therefore, according to this embodiment, a high-quality thermoelectric conversion element can be easily realized.
[0039] The thermoelectric conversion film may be a film obtained by applying a thermoelectric conversion material onto a substrate. Since the thermoelectric conversion material has excellent formability, it is easy to obtain a good film by the application method. A wet film formation method is mainly used for forming the thermoelectric conversion film. Specifically, a method using various means such as a spin coating method, a spray method, a roller coating method, a gravure coating method, a die coating method, a comma coating method, a roll coating method, a curtain coating method, a bar coating method, an inkjet method, a dispenser method, silk screen printing, and flexographic printing can be mentioned. The above methods can be appropriately selected according to the thickness to be applied and the viscosity of the material.
[0040] The thickness of the thermoelectric conversion film is not particularly limited, but is preferably formed to have a certain thickness or more so that a temperature difference can be generated and transmitted in the thickness direction or surface direction of the thermoelectric conversion film, as described later. In one embodiment, from the viewpoint of thermoelectric properties, the thickness of the thermoelectric conversion film is preferably in the range of 0.1 to 200 μm, more preferably in the range of 1 to 100 μm, and further preferably in the range of 1 to 50 μm.
[0041] In addition, the substrate to which the thermoelectric conversion material is applied may be a plastic film made of a material such as polyethylene, polyethylene terephthalate, polyethylene naphthalate, polyethersulfone, polypropylene, polyimide, polycarbonate, or cellulose triacetate, or glass.
[0042] In order to improve the adhesion between the substrate and the thermoelectric conversion film, various treatments can be performed on the substrate surface. Specifically, prior to application of the thermoelectric conversion material, UV ozone treatment, corona treatment, plasma treatment, or adhesion enhancing treatment may be performed.
[0043] The thermoelectric conversion element according to the embodiment of the present invention can be constructed by applying techniques well known in the art, except that it is constructed using the above-mentioned thermoelectric conversion material. A more specific configuration of the thermoelectric conversion element and a manufacturing method thereof will be described as a representative example.
[0044] In one embodiment, the thermoelectric conversion element has a thermoelectric conversion film obtained by using a thermoelectric conversion material, and a pair of electrodes connected to the thermoelectric conversion film in an electrode-like manner. Here, "electrically connected" means that they are joined to each other or can be electrically connected via other components such as wires.
[0045] The material of the electrode can be selected from metals, alloys, and semiconductors. In one embodiment, metals and alloys are preferred because they have high electrical conductivity and low contact resistance with the thermoelectric conversion material according to the present invention constituting the thermoelectric conversion film. As a specific example, the electrode preferably contains at least one selected from the group consisting of gold, silver, copper, and aluminum. It is more preferred that the electrode contains silver.
[0046] The electrodes can be formed by a method such as vacuum deposition, thermocompression bonding of an electrode material foil or a film having an electrode material film, application of a paste in which fine particles of the electrode material are dispersed, etc. From the viewpoint of process simplicity, the method of thermocompression bonding of an electrode material foil or a film having an electrode material film, or application of a paste in which the electrode material is dispersed is preferred. EXAMPLES
[0047] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the examples, "parts" means "parts by mass" and "%" means "% by mass" unless otherwise specified. In addition, "NMP" refers to N-methylpyrrolidone.
[0048] <Synthesis of organic semiconductor B> (Synthesis Example 1) To the flask, 20 mL of toluene, 56.1 mmol (5.0 g) of dimethylaminoethanol, and 112 mmol (13.3 g) of triethylamine were added and stirred in an ice bath. 168 mmol (17.0 g) of thionyl chloride was added dropwise over 30 minutes, and the mixture was stirred for 2 hours after the dropwise addition. The temperature of the flask was brought to 25°C, and the mixture was stirred for an additional 4 hours. 50 mL of 10% aqueous sodium hydroxide solution was added to the reaction solution, which was stirred, and the precipitate was filtered. The filtrate was washed twice with 200 mL of water and once with 100 mL of saturated saline. The washed reaction solution was poured into a flask, and 56.1 mmol (6.8 g) of 4-hydroxybenzaldehyde and 56.1 mmol (7.8 g) of potassium carbonate were added, followed by heating under reflux for 4 hours. The reaction solution was dried under reduced pressure, dissolved in tetrahydrofuran, and separated by silica gel column chromatography to obtain intermediate product (A-1). 15.5 mmol (3.0 g) of intermediate product (A-1), 6.2 mmol (0.7 g) of rubeanic acid, and 10 g of dimethylformamide were added to a flask and heated under reflux for 8 hours. The reaction solution was mixed with 200 g of methanol, and the precipitate was filtered off. The precipitate was dried under reduced pressure to obtain intermediate product (B-1). 1.0 g of intermediate product (B-1) was mixed with 10 g of methyl iodide, and stirred at 25°C for 2 hours. The precipitate was collected by filtration to obtain product 1 of Synthesis Example 1.
[0049] (Synthesis Examples 2 to 10) Intermediate products (A-2) to (A-10), intermediate products (B-2) to (B-10), and products 2 to 10 shown in Table 1 were obtained in the same manner as in Synthesis Example 1, except that dimethylaminoethanol was replaced with an amine shown in Table 1. The amines used were in the same molar amounts as in Synthesis Example 1.
[0050] (Synthesis Example 11) 6.4 mmol (1.5 g) of intermediate product (A-1), 6.4 mmol (1.6 g) of intermediate product (A-2), 5.1 mmol (0.6 g) of rubeanic acid, and 10 g of dimethylformamide were added to a flask and heated under reflux for 8 hours. The reaction solution was mixed with 200 g of methanol, and the precipitate was filtered off. The precipitate was dissolved in tetrahydrofuran and separated by silica gel chromatography to obtain intermediate product (B-11). 1.0 g of intermediate product (B-11) was mixed with 10 g of methyl iodide and stirred at 25°C for 2 hours. The precipitate was collected by filtration to obtain product 11 of Synthesis Example 11.
[0051] (Synthesis Examples 12 to 16) Intermediate products (B-12) to (B-16) and products 12 to 16 shown in Table 2 were obtained in the same manner as in Synthesis Example 11, except that intermediate product (A-1) and intermediate product (A-2) were changed to the combination of intermediate product A shown in Table 2. The molar amount of intermediate product A used was the same as in Synthesis Example 11.
[0052] (Synthesis Example 17) 1.0 g of the intermediate product (B-1) was mixed with 10 g of ethyl iodide and stirred for 2 hours at 25° C. The precipitate was collected by filtration to obtain Product 17 of Synthesis Example 17. (Synthesis Examples 18-24) Products 18 to 24 were obtained in the same manner as in Synthesis Example 17, except that intermediate product B and methyl iodide were changed to intermediate product B and alkyl iodide in Table 3.
[0053] (Synthesis Example 25) To the flask, 20 mL of toluene, 20 mL of sulfuric acid, 36.5 mmol (3.26 g) of dimethylaminoethanol, and 12.2 mmol (2.0 g) of methyl terephthalaldehyde were added, and the mixture was stirred for 8 hours while being heated at 100°C. 50 mL of 10% aqueous sodium hydroxide solution and 50 mL of toluene were added to the reaction solution, and the toluene layer was taken out. The taken out toluene solution was washed twice with 200 mL of ion-exchanged water and once with 100 mL of saturated saline. The toluene solution was dried under reduced pressure, then dissolved in tetrahydrofuran and separated by silica gel column chromatography to obtain intermediate product (A-25). 13.6 mmol (3.0 g) of intermediate product (A-25), 5.1 mmol (0.7 g) of rubeanic acid, and 10 g of dimethylformamide were added to a flask and heated under reflux for 8 hours. The reaction solution was mixed with 200 g of methanol, and the precipitate was filtered off. The precipitate was dried under reduced pressure to obtain intermediate product (B-25). 1.0 g of intermediate product (B-25) was mixed with 10 g of methyl iodide, and stirred at 25°C for 2 hours. The precipitate was collected by filtration to obtain product 25 of Synthesis Example 25.
[0054] (Synthesis Examples 26 to 34) Intermediate products (A-26) to (A-34), intermediate products (B-26) to (B-34), and products 26 to 34 in Table 4 were obtained in the same manner as in Synthesis Example 25, except that the amine used was changed to the amine in Table 4. The amine used was in the same molar amount as in Synthesis Example 25.
[0055] (Synthesis Examples 35-40) Intermediate products (B-35) to (B-40) and products 35 to 40 in Table 5 were obtained in the same manner as in Synthesis Example 11, except that the combination of intermediate products A used was changed to those shown in Table 5. The molar amount of intermediate product A used was the same as in Synthesis Example 11.
[0056] (Synthesis Examples 41 to 48) Products 41 to 48 in Table 6 were obtained in the same manner as in Synthesis Example 17, except that intermediate product B and methyl iodide were changed to intermediate product B and alkyl iodide in Table 6.
[0057] (Synthesis Examples 49-58) Intermediate products (A-49) to (A-58), intermediate products (B-49) to (B-58), and products 49 to 58 in Table 7 were obtained in the same manner as in Synthesis Example 25, except that the amine used was changed to the amine in Table 7. The molar amounts of the amine used were the same as in Synthesis Example 25.
[0058] (Synthesis Examples 59-64) Intermediate products (B-59) to (B-64) and products 59 to 64 in Table 8 were obtained in the same manner as in Synthesis Example 11, except that the combination of intermediate products A used was changed to the intermediate products A listed in Table 8. The molar amount of intermediate product A used was the same as in Synthesis Example 11.
[0059] (Synthesis Examples 65-72) Products 65 to 72 in Table 9 were obtained in the same manner as in Synthesis Example 17, except that intermediate product B and methyl iodide were changed to intermediate product B and alkyl iodide in Table 9.
[0060] (Synthesis Example 73) 20 mL of toluene, 20 mL of sulfuric acid, 49.1 mmol (5.1 g) of N,N-dimethylglycine, and 16.4 mmol (2.0 g) of 4-hydroxybenzaldehyde were added to a flask and stirred for 8 hours while heating at 100°C. 50 mL of 10% aqueous sodium hydroxide solution and 50 mL of toluene were added to the reaction solution, and the toluene layer was removed. The removed toluene solution was washed twice with 200 mL of ion-exchanged water and once with 100 mL of saturated saline. The toluene solution was dried under reduced pressure, then dissolved in tetrahydrofuran and separated by silica gel column chromatography to obtain intermediate product (A-73). 14.5 mmol (3.0 g) of intermediate product (A-73), 5.8 mmol (0.7 g) of rubeanic acid, and 10 g of dimethylformamide were added to a flask and heated under reflux for 8 hours. The reaction solution was mixed with 200 g of methanol, and the precipitate was filtered off. The precipitate was dried under reduced pressure to obtain intermediate product (B-73). 1.0 g of intermediate product (B-73) was mixed with 10 g of methyl iodide, and stirred at 25°C for 2 hours. The precipitate was collected by filtration to obtain product 73 of Synthesis Example 73.
[0061] (Synthesis Examples 74-82) The intermediate products (A-74) to (A-82), intermediate products (B-74) to (B-82), and products 74 to 82 in Table 10 were obtained in the same manner as in Synthesis Example 73, except that the amine used was changed to the amine in Table 10. The molar amount of the amine used was the same as in Synthesis Example 25.
[0062] (Synthesis Examples 83-88) Intermediate products (B-83) to (B-88) and products 83 to 88 in Table 11 were obtained in the same manner as in Synthesis Example 11, except that the combination of intermediate products A used was changed to those shown in Table 11. The molar amount of intermediate product A used was the same as in Synthesis Example 11.
[0063] (Synthesis Examples 89-96) Products 89 to 96 in Table 12 were obtained in the same manner as in Synthesis Example 17, except that intermediate product B and methyl iodide were changed to intermediate product B and alkyl iodide in Table 12.
[0064] (Synthesis Examples 97-106) The intermediate products (A-97) to (A-106), intermediate products (B-97) to (B-106), and products 97 to 106 in Table 13 were obtained in the same manner as in Synthesis Example 73, except that the amine used was changed to the amine in Table 13 and 4-hydroxybenzaldehyde was changed to 4-aminobenzaldehyde. The amine used was the same molar amount as in Synthesis Example 73. The 4-aminobenzaldehyde was the same molar amount as the 4-hydroxybenzaldehyde used in Synthesis Example 73.
[0065] (Synthesis Examples 107-112) Intermediate products (B-107) to (B-112) and products 107 to 112 in Table 14 were obtained in the same manner as in Synthesis Example 11, except that the combination of intermediate products A used was changed to that in Table 14. The molar amount of intermediate product A used was the same as in Synthesis Example 11.
[0066] (Synthesis Examples 113-120) Products 113 to 120 in Table 15 were obtained in the same manner as in Synthesis Example 17, except that intermediate product B and methyl iodide were changed to intermediate product B and alkyl iodide in Table 15.
[0067] (Synthesis Example 121) 1 g of product 1, 10 g of 35% hydrochloric acid, and 10 g of tetrahydrofuran were added to a flask and treated with an ultrasonic cleaner for 10 minutes. The dispersion was stirred at 50°C for 4 hours. The resulting dispersion was filtered, and the separated solid was washed with tetrahydrofuran to obtain a chloride ion-substituted product of product 1 in which the iodide ions in product 1 were replaced with chloride ions.
[0068] (Synthesis Examples 122-144) Except for changing Product 1 to a product shown in Table 16, the same method as in Synthesis Example 121 was used to obtain chloride ion-substituted products of Products 2 to 24, respectively.
[0069] (Synthesis Examples 145-168) Except for changing Product 1 to a product shown in Table 17 and changing 35% hydrochloric acid to 45% hydrobromic acid, the same method as in Synthesis Example 121 was used to obtain bromide ion-substituted products of Products 1 to 24, respectively.
[0070] (Synthesis Examples 169-192) Substitution products of anion 1 having the following structures, products 1 to 24, were obtained in the same manner as in Synthesis Example 121, except that product 1 was changed to a product shown in Table 18 and 35% hydrochloric acid was changed to acetic acid.
[0071] [ka]
[0072] (Synthesis Examples 193-216) Substitution products of anion 2 having the following structures, products 1 to 24, were obtained in the same manner as in Synthesis Example 121, except that product 1 was changed to a product shown in Table 19 and 35% hydrochloric acid was changed to 42% tetrafluoroboric acid.
[0073] [ka]
[0074] (Synthesis Examples 217-240) Substitution products of anion 3 having the following structures, products 1 to 24, were obtained in the same manner as in Synthesis Example 121, except that product 1 was changed to a product shown in Table 20 and 35% hydrochloric acid was changed to sodium tetrakispentafluorophenylborate.
[0075] [ka]
[0076] (Synthesis of phenylthiazolothiazole) 15.5 mmol (1.64 g) of benzaldehyde, 6.2 mmol (0.7 g) of rubeanic acid, and 10 g of dimethylformamide were added to a flask and heated under reflux for 8 hours. The reaction solution was mixed with 200 g of methanol, and the precipitate was filtered off. The precipitate was dried under reduced pressure to obtain phenylthiazolothiazole having the following structure.
[0077] [ka]
[0078] (Comparative compound 1) 23.9 mmol (5 g) of 9-dimethylaminofluorene was mixed with 20 g of methyl iodide and stirred at 25° C. for 2 hours. The resulting dispersion was mixed with 500 g of methanol, and the precipitate was collected by filtration. The collected precipitate was dried under reduced pressure to obtain a comparative compound 1 having the following structure.
[0079] [ka]
[0080] <Production of thermoelectric conversion materials> [Example 1] (Dispersion 1) 0.4 parts of single-walled carbon nanotubes "TUBALL" (abbreviated as SWCNT) manufactured by OCSiAl Corporation were weighed and mixed as conductive material A, 0.4 parts of product 1 as organic semiconductor B, and 79.2 parts of NMP. Furthermore, 140 parts of zirconia beads (φ1.25 mm) were added, and the mixture was shaken with a Scandex for 2 hours, after which the zirconia beads were removed by filtration, and dispersion liquid 1 of a thermoelectric conversion material was obtained.
[0081] [Examples 2 to 240, Comparative Examples 1 to 2] (Dispersion 2~240, comparative dispersion 1~2) Thermoelectric conversion material dispersions 2 to 240 and comparative dispersions 1 and 2 were obtained in the same manner as in Example 1, except that the type of organic semiconductor B was changed to that shown in Tables 21 and 22. As comparative compound 2, [sulfanediylbis(4,1-phenylene)]bis(diphenylsulfonium)=bis(hexafluoro-λ5-stibanide) was used.
[0082] [Examples 241 to 360] (Dispersion 241~360) Except for changing the type and amount of organic semiconductor B to those shown in Table 23, the same procedure as in Example 1 was carried out to obtain dispersions 241 to 312 of thermoelectric conversion materials.
[0083] [Examples 361 to 432] (Dispersion liquid 361~432) Dispersions 361 to 432 of thermoelectric conversion materials were obtained in the same manner as in Example 1, except that the type and amount of organic semiconductor B was changed to those shown in Table 24, and phenylthiazolothiazole was added as an additional component during mixing in the amount shown in Table 24.
[0084] [Examples 433 to 504] (Dispersion liquid 433~504) Except for changing the type of conductive material A, the type of organic semiconductor and its blending amount to those shown in Table 25, the same procedure as in Example 1 was carried out to obtain dispersions 433 to 504 of thermoelectric conversion materials. The abbreviations in the table are as follows. Graphite: Nippon Graphite Co., Ltd. graphite "CPB" MWCNT: Multi-walled carbon nanotube "100P" manufactured by Knano GNP: Graphene nanoplatelets "xGNP-M-5" manufactured by XG Sciences
[0085] <Evaluation of liquid stability of dispersion> 20 mL of the dispersion was transferred to a cylindrical glass container and left to stand at 25° C. for one week. After standing, the volume ratio of the supernatant of the dispersion resulting from the precipitation of the conductive material A to the entire dispersion was measured. If the ratio of the transparent portion was 20% by volume or less, it was at a practical level. ◎: The percentage of transparent areas is 5% or less by volume (very good) ○: The ratio of transparent parts is more than 5% by volume and less than 10% by volume (good) △: The percentage of transparent parts is greater than 10% by volume and less than 20% by volume (practical) ×: The ratio of transparent parts is more than 20% by volume (not practical).
[0086] <Evaluation of Thermoelectric Conversion Materials> The obtained dispersions 1 to 504 and comparative dispersions 1 to 2 were each applied to a polyethylene terephthalate (PET) film having a thickness of 75 μm, which was a sheet-like substrate, using an applicator, and then heated and dried at 120° C. for 30 minutes to obtain a laminate having a thermoelectric conversion film having a thickness of 5 μm on the PET substrate. The electrical conductivity, Seebeck coefficient, and power factor (PF) of the obtained laminate having a thermoelectric conversion film (hereinafter also referred to as a coating film) were evaluated as follows. The results are shown in Tables 21 to 25.
[0087] (conductivity) The obtained laminate was cut into a size of 2.5 cm x 5 cm, and the resistivity was measured by a four-terminal method using Loresta GX MCP-T700 (manufactured by Mitsubishi Chemical Analytech Co., Ltd.) in accordance with JIS-K7194. Then, the conductivity, which is the reciprocal of the resistivity, was calculated.
[0088] (Seebeck coefficient) The obtained laminate was cut into a size of 3 mm x 10 mm, and silver paste (REXALPHA RA FS 074, manufactured by Toyochem Co., Ltd.) was applied to the 2 mm area on both ends of the cut laminate to create a thermoelectric conversion element. The Seebeck coefficient (μV / K) at 80°C was measured as the thermoelectric conversion performance using ZEM-3LW manufactured by Advance Riko Co., Ltd.
[0089] (Power Factor (PF)) Using the obtained conductivity and Seebeck coefficient, the PF (=S 2 σ) was calculated and evaluated according to the following criteria: PF is 2.5μW / (mK 2) or higher is considered to be at a practical level. ◎: PF is 20μW / (mK 2 ) or better (very good) ○: PF is 10μW / (mK 2 ) or more, 20μW / (mK 2 ) (Good) △: PF is 2.5μW / (mK 2 ) or more, 10μW / (mK 2 ) (practical) ×: PF is 2.5μW / (mK 2 ) (not practical)
[0090] [Table 1]
[0091] [Table 2]
[0092] [Table 3]
[0093] [Table 4]
[0094] [Table 5]
[0095] [Table 6]
[0096] [Table 7]
[0097] [Table 8]
[0098]
Table 9
[0099]
Table 10
[0100]
Table 11
[0101]
Table 12
[0102]
Table 13
[0103]
Table 14
[0104]
Table 15
[0105]
Table 16
[0106]
Table 17
[0107]
Table 18
[0108]
Table 19
[0109]
Table 20
[0110]
Table 21
[0111]
Table 22
[0112]
Table 23
[0113]
Table 24
[0114]
Table 25
[0115]
Table 26
[0116]
Table 27
[0117]
Table 28
[0118]
Table 29
Claims
1. A thermoelectric conversion material comprising a conductive material A and an organic semiconductor B, the organic semiconductor B being represented by the following general formula (1): 【Chemistry 1】 [In the general formula (1), m and n each independently represent an integer of 1 to 12. 1 , R 2 , R 3 , R 4 , R 5 and R 6 each independently represents an alkyl group, 1 , R 2 and R 3 Any two or more of the above and R 4 , R 5 and R 6 Any two or more of X may be bonded to each other directly or via an oxygen atom to form a ring. - represents an anion. 1 and Y 2 each independently represents an oxygen atom, an oxyalkylene group, -COO-, -CONH-, or a divalent linking group formed by these groups.]
2. 2. The thermoelectric conversion material according to claim 1, wherein the content of the organic semiconductor B is 10 to 100 mass % based on the total amount of the conductive material A.
3. 3. The thermoelectric conversion material according to claim 1, wherein m and n are each independently an integer of 1 to 7.
4. X - 4. The thermoelectric conversion material according to claim 1, wherein is a halide ion.
5. A thermoelectric conversion element comprising a thermoelectric conversion film made of the thermoelectric conversion material according to any one of claims 1 to 4 and electrodes, the thermoelectric conversion film and the electrodes being electrically connected to each other.
Citation Information
Patent Citations
Material for organic electroluminescent element, and organic electroluminescent element
JP2007314757A
Thermoelectric conversion material, and thermoelectric conversion element prepared therewith
JP2020098899A
Thermoelectric conversion material and thermoelectric conversion element
JP2021090038A
Thermoelectric conversion material and thermoelectric conversion element
WO2015050113A1
Thermoelectric conversion material and thermoelectric conversion element
WO2015129877A1